MODEL ALOKASI ANGGARAN URUSAN PEMERINTAHAN BIDANG SOSIAL DALAM RANGKA MENINGKATKAN PERAN PEMERINTAH KABUPATEN/KOTA DALAM PENANGANAN MASALAH SOSIAL - Syahlan Syahlan (Jurnal Good Governance, 2018)
Regional autonomy in fact intended to speed up realization of the welfare society, in addition to the efficiency and effectiveness of the implementation of governance through improved services and empowerment community, which is based on the principle of democracy, justice and equitable accordance aspirations of the region. Law Number 23 of 2014 reinforce that point of regional autonomy at kabupaten/kota, according to principles and affairs criteria between levels of government. This case implicates against financing and organizing government budget allocation in the region. Focus of this study is budget allocations of government affairs to the social field for enhancement the role of kabubaten/kota government in handling of social problems. Results of the study, concluded that model of budget allocation to organizing government affairs of the social field, should be funded through a Dana Alokasi Khusus (DAK), because: 1) According the principles and criteria affair between levels of government, authority of social field basically is affairs of kabupaten/kota government, 2) kabupaten/kota governments will be able to determine target of the program according to the needs and kabupaten/kota priority, 3) Management of the budget can be effective and efficient if managed by single entity with APBD management.Keyword: decentralization, social affairs, allocate budget.